Impact of canalplasty on the surgical outcomes of type-1 tympanoplasty: experience in a tertiary care teaching hospital - Das SR; Baliarsingh P; Bhattacharyya B; Das S; Padhy RN (Ibom Medical Journal)
Context: Canalplasty restores the normal width and shape of the external auditory canal (EAC) for passage of sound. It is required as a co-surgical procedure with tympanoplasty in some cases; where the entire tympanic membrane and anulus cannot be seen during surgery due to the bony overhang or narrowing.